Optimization Of The State Sukuk As An Instrument Of Natural Gas Downstream Financing To Support National Energy Security - Wartowiyono, Sudadi Sugi; Ascarya, Ascarya (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2025)
Limited funding for downstream natural gas infrastructure challenges Indonesia’s energy security. Relying on the State Budget (APBN) amid rising investment needs, this study explores state sukuk (Islamic bonds) as an alternative financing tool during a sustainable energy transition. Using a descriptive-qualitative approach, it analyzes secondary data from ministries, sukuk reports, literature, and interviews with seven experts (regulators), academics, and practitioners. Data analysis involved content analysis and the Analytic Network Process (ANP) to identify problems, priorities, and strategies. Results show regulatory gaps, limited financing, and immature project planning are key obstacles. State Sukuk is promising due to its asset-backed, Sharia-compliant nature and ability to attract investors, though its use is low compared to other methods. Findings highlight the need for consistent policies, robust economic assessments, and pilot projects to enhance Islamic finance's role in energy security. This study provides empirical insights into Sukuk Negara's strategic importance for Indonesia’s downstream natural gas infrastructure, integrates stakeholder perspectives with ANP, and offers a framework for policy development and future sharia-compliant energy financing.